INFORMATION TECHNOLOGY AND ITS RELATIONSHIP TO THE EFFICIENCY OF THE ADMINISTRATIVE PERFORMANCE OF THE ADMINISTRATIVE BODIES IN THE CLUBS OF THE IRAQI MINISTRY OF INTERIOR - Assistant Professor Dr. Rana Turki Naji (Galaxy International Interdisciplinary Research Journal, 2023)
The researcher conducted her current study on a sample of members of the administrative bodies of clubs affiliated to the Iraqi Ministry of Interior. Amendment and the steps of scientific research work from fulfilling all its conditions and after distributing the questionnaires to the target sample and conducting statistical treatments of the data obtained by the researcher through the answers of the respondents. She reached many results and conclusions. Among which there is a high correlation between in formation technology and the research sample and the weakness of efficiency of administrative performance in the guidance to work on the development of technology made it possible through practical and modern scientific practices to gain information and circulate it. In the light of these results and conclusions, the researcher made several recommendations, including: Adopting the standards and levels that the researcher reached in other studies. He urged members of the administrative bodies to participate in developmental courses in the field of modern technology and methods of communication and communication with the outside world.